2019
DOI: 10.1155/2019/2682748
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gut Microbiota in the Pharmacological Effects of Natural Products

Abstract: Increasing evidence has demonstrated that natural products derived from traditional Chinese medicine, such as ginseng, berberine, and curcumin, possess a wide variety of biological activities on gut microbiota, which may cause changes in the composition of intestinal microbiota, microbial metabolites, intestinal tight junction structure, and mucosal immunology. These changes will eventually result in the exertion of the pharmacological effects by treatment with these natural products. In this review, we will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 89 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…These compounds are well known to bring beneficial effects to the host by affecting metabolic activities of its gut microbiota. Many previous studies have shown that natural products exert pharmacological effects by modulating the composition of gut microbiota [22,23,24]. Likewise, the potential beneficial effects of JGT on colitis may be partially related to its interaction with gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are well known to bring beneficial effects to the host by affecting metabolic activities of its gut microbiota. Many previous studies have shown that natural products exert pharmacological effects by modulating the composition of gut microbiota [22,23,24]. Likewise, the potential beneficial effects of JGT on colitis may be partially related to its interaction with gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence supports that the gut microbiome plays pivotal roles in cancer malignancy, via a primary mechanism influencing anti-tumor immunosurveillance [ 51 , 52 ]. Meanwhile, emerging evidence also supports broad pharmacological effects of natural products on gut microbiota, including the microbiota composition, microbial metabolites, intestinal tight junction structure, and mucosal immunology [ 53 ]. In-depth understanding in this regard may resolve a long puzzle of why most natural products exhibit concrete pharmacological effects despite the very limited plasma and tumor exposure.…”
Section: Future Directions That May Open New Opportunities For Naturamentioning
confidence: 99%
“…Given the eubiotic properties of rifamycin and berberine[ 24 , 25 ], this patient was prescribed successive administration of rifampicin (450 mg, once per day) and berberine (0.3 g, thrice per day) with monthly administered GCP (1500 mL polyethylene glycol electrolyte solution per day for 2 d) after his third recurrence. Other employed drugs included lactulose oral solution (45-50 mL per day), inulin (15-20 g per day), and probiotics consisting of Lactobacillus acidophilus, Clostridium butyricum, Bifidobacterium, Bacillus coagulans, and Enterococcus .…”
Section: To the Editormentioning
confidence: 99%